2019
DOI: 10.1007/s13193-019-00875-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radicality Versus Timing of Surgery in Patients with Advanced Ovarian Cancer (Stage III C) Undergoing CRS and HIPEC—a Retrospective Study by INDEPSO

Abstract: HIPEC in addition to interval CRS has shown a survival benefit of 12 months compared to CRS alone. However, there are many controversial issues pertaining to CRS itself which should be addressed first. To compare NACT and primary CRS approaches when CRS is categorized according to the extent of resection. To evaluate the feasibility of performing HIPEC at these two time points. A retrospective analysis of patients with stage III C ovarian cancer undergoing primary and interval CRS + HIPEC was performed. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this series of patients with diffuse peritoneal metastases at diagnosis from primary advanced tubo‐ovarian HGSC who underwent UDS or NACT‐IDS with peritonectomy procedures both followed by HIPEC in centers experienced in treating PSM, the two cytoreductive procedures, as Bhatt et al, reported led to similar outcomes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In this series of patients with diffuse peritoneal metastases at diagnosis from primary advanced tubo‐ovarian HGSC who underwent UDS or NACT‐IDS with peritonectomy procedures both followed by HIPEC in centers experienced in treating PSM, the two cytoreductive procedures, as Bhatt et al, reported led to similar outcomes.…”
Section: Discussionmentioning
confidence: 64%
“…After the study by Van Driel et al was published, despite criticisms, hyperthermic intraperitoneal chemotherapy (HIPEC) intended to complete cytoreductive surgical efforts began to gather interest also in the gynecological oncology community . Only one study published to date has investigated outcomes in a series that compares patients who underwent UDS versus NACT‐IDS treated with cytoreduction according to peritonectomy procedures both combined with HIPEC . Knowing whether this combined approach influences outcomes related to UDS or NACT IDS, including the site of recurrence, could help to improve therapeutic strategies in centers experienced in treating peritoneal surface malignancies (PSM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that more extensive surgery following neoadjuvant chemotherapy can in part offset the poor prognostic impact of a poor response to systemic chemotherapy and this should be further evaluated. [22]…”
Section: Addressing Residual Disease After Neoadjuvant Chemotherapymentioning
confidence: 99%
“…It is possible that more extensive surgery following neoadjuvant chemotherapy can in part offset the poor prognostic impact of a poor response to systemic chemotherapy and this should be further evaluated. [22] Addressing regional nodes Though a recent randomized trial showed no benefit of systematic lymphadenectomy when nodes were not enlarged, this trial is only for surgery performed upfront and not for surgery following neoadjuvant chemotherapy. [23] Hence, in our opinion, there is no clear directive as to which patients should have regional lymphadenectomy following neoadjuvant chemotherapy.…”
Section: Addressing Residual Disease After Neoadjuvant Chemotherapymentioning
confidence: 99%